The global smart city : challenges and opportunities in the digital age - Marchesani, Filippo (Emerald Publishing Limited, 2023)
The Global Smart City: Challenges and Opportunities in the Digital Age is a ground-breaking exploration of the transformative impact of smart cities in today's urban landscape. Through a comprehensive analysis of smart city projects, this study sheds light on the urban, economic, and competitive outcomes of integrating new technologies. Divided into two parts, this in-depth study provides fresh insights into the ongoing smart city debate. In Part 1, author Filippo Marchesani explores the internal implementation of smart city projects, analyzing digital implementation, the dimensions of smart cities, and the geographic factors influencing their adoption. Drawing on international contributions and primary research across various disciplines, such as digital technologies, architecture, economics, regional studies, and innovation, this section fills a crucial gap in the academic debate, offering a comprehensive theoretical and analytical foundation. Part 2 shifts focus to the urban, economic, and competitive outcomes of smart city initiatives, employing a multidisciplinary approach. It examines the tangible effects of these projects on the urban environment, economic landscape, and overall city attractiveness, utilizing real-world examples and data-driven methodologies. The Global Smart City: Challenges and Opportunities in the Digital Age is essential reading for policymakers, urban planners, technologists, academics, and anyone interested in the dynamic changes unfolding in our cities and society. With his unique interdisciplinary perspective and wealth of research, Marchesani offers a comprehensive exploration of smart cities, empowering readers to embrace the challenges and opportunities that lie ahead.
Includes index.
Keywords: Smart cities.; Business & Economics -- Urban & Regional.; Sustainability.; elektronické knihy; electronic books